Intestinal perforation in premature neonates: The need for subsequent laparotomy after placement of peritoneal drains. (29th October 2015) - Mishra, Prabal; Foley, David; Purdie, Gordon; Pringle, Kevin C
Abstract : Aim: In view of recent studies questioning the usefulness of peritoneal drainage (PD) in premature neonates with pneumoperitoneum, suggesting approximately 75% of those treated with PD needed delayed laparotomy, we reviewed the requirement for laparotomy after initial PD at our institution. Methods: Retrospective cohort of all premature infants with a diagnosis of intestinal perforation (ICD Code P78.0) from 1995 to 2012. Inclusion criteria were pneumoperitoneum on x‐ray (isolated perforation or necrotising enterocolitis), birthweight <1800 g and gestational age <33 weeks. Results: Fifty patients met the criteria (38 PD, 12 primary laparotomy). Thirty‐two per cent (95% CI 18–49%) received secondary laparotomy after initial PD. There was no significant difference when stratified according to isolated perforation (24%) versus necrotising enterocolitis (56%, P = 0.11). There was no significant difference between PD and primary laparotomy for time to full enteral nutrition, hazard ratio (HR) 0.99 (95% CI 0.48–2.04) or mortality, HR 2.15 (95% CI 0.48–9.63). The HR for mortality was partly confounded by birthweight, birthweight‐adjusted HR 1.52 (95% CI 0.32–7.23). Conclusions: Thirty‐two per cent of neonates treated with primary PD received secondary laparotomy, with no significant difference in key outcomes. Primary PD still appears to be of benefit for those without features of necrotising enterocolitis.